Lobbying and Negotiation Communication Strategy at Film The Negotiation - Annisa Septi Savitri; Ellyana Gustirani; Kaila Andrena Yogiswara; Dini Safitri (Jurnal Komunikasi dan Bisnis, 2023)
Globalization's huge expansion of information technology has become a crucial component in the Indonesian people's desire for Hallyu. Hallyu is linked with the realm of entertainment, including music, theater, cinema, and a variety of programs beautifully packaged to promote Korean culture. The growth of South Korean films may also be witnessed in how overseas viewers can appreciate them. The Negotiation, for example, is able to reach the Indonesian market and is available on the local video-on-demand streaming program, Vidio. There are a variety of lobbying and negotiation strategies which can be linked to The Negotiation. Five scenes and dialogues with messages related to communication techniques and business negotiations were selected and analyzed using the semiotic theory of Ferdinand De Saussure's model. A qualitative approach is used in this research procedure. This qualitative research adheres to the symbolic interactionism paradigm, which views human activity as the construction of meaning.